2013
DOI: 10.3727/096368912x658953
|View full text |Cite
|
Sign up to set email alerts
|

Sciatic Nerve Regeneration by Cocultured Schwann Cells and Stem Cells on Microporous Nerve Conduits

Abstract: Cell transplantation is a useful therapy for treating peripheral nerve injuries. The clinical use of Schwann cells (SCs), however, is limited because of their limited availability. An emerging solution to promote nerve regeneration is to apply injured nerves with stem cells derived from various tissues. In this study, different types of allogeneic cells including SCs, adipose-derived adult stem cells (ASCs), dental pulp stem cells (DPSCs), and the combination of SCs with ASCs or DPSCs were seeded on nerve cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
87
4
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(103 citation statements)
references
References 54 publications
(62 reference statements)
5
87
4
3
Order By: Relevance
“…We showed that Schwann cell-like differentiated ASC could enhance motor neuron regeneration and improve evoked electrical potentials in the gastrocnemius muscle [26] and also at early stages of regeneration, we observed a down-regulation of apoptotic markers in the DRG which was suggestive of a pro-survival effect [29]. Undifferentiated rat ASC have also been shown to enhance peripheral nerve repair [28,30], and they may act synergistically with Schwann cells to secrete growth factors such as NGF [25]. Alternatively, the stem cells can be neurally induced to release enhanced levels of BDNF, which is necessary for their nerve stimulatory effects [27].…”
Section: Stimulated Asc Enhance Nerve Repairmentioning
confidence: 76%
See 1 more Smart Citation
“…We showed that Schwann cell-like differentiated ASC could enhance motor neuron regeneration and improve evoked electrical potentials in the gastrocnemius muscle [26] and also at early stages of regeneration, we observed a down-regulation of apoptotic markers in the DRG which was suggestive of a pro-survival effect [29]. Undifferentiated rat ASC have also been shown to enhance peripheral nerve repair [28,30], and they may act synergistically with Schwann cells to secrete growth factors such as NGF [25]. Alternatively, the stem cells can be neurally induced to release enhanced levels of BDNF, which is necessary for their nerve stimulatory effects [27].…”
Section: Stimulated Asc Enhance Nerve Repairmentioning
confidence: 76%
“…Transplantation of rat ASC in nerve conduits promotes nerve regeneration, enhances nerve conduction velocities, and reduces muscle atrophy and sensory neuron cell death after sciatic nerve injury [25][26][27][28][29][30]. To date, only a few reports show these results can be replicated using human ASC.…”
mentioning
confidence: 85%
“…Unfortunately, in those studies a direct comparison with differentiated cells was not made. An alternative approach has been to use undifferentiated stem cells transplanted in coculture with Schwann cells, which gives better functional and morphological results than using ADSCs alone [Dai et al, 2013]. Another route to clinical translation might be to bypass the use of living cells and instead isolate exosomes/microvesicles from the cells.…”
Section: Later Time Points: Myelinated Fiber Counts Electrophysiologmentioning
confidence: 99%
“…The cytokine CXCL5 is produced abundantly by ADSCs and is responsible for promoting neurite outgrowth from rat major pelvic ganglia and stimulating signaling cascades in Schwann cells [Zhang et al, 2011]. Coculture of Schwann cells and ADSCs synergistically upregulates the expression of NGF, BDNF and glial cellderived neurotropic factor (GDNF) [Dai et al, 2013]. Both undifferentiated stem cells and those treated with stimulating factors can induce neurite outgrowth, but only the later type can form myelin in vitro [Wei et al, 2010].…”
Section: Adscs and Secreted Growth Factorsmentioning
confidence: 99%
“…Dai et al . tested the efficacy of different types of allogeneic cells including SCs, ASCs, dental pulp stem cells (DPSCs), and the combination of SCs with ASCs or DPSCs seeded on nerve conduits to repair rat sciatic nerves [13]. A combination of SCs and ASCs or DPCs resulted in the greatest functional recovery, as evaluated by walking track, functional gait, nerve conduction velocity, and histological analysis.…”
Section: Introductionmentioning
confidence: 99%